Locating Land for Special Economic Zones: a Methodology. - Ramachandran, H. and Biswas, Debatosh (2007)
This paper focuses on the possible locations of Special Economic Zones (SEZs) and develops a set of criteria and methodology of identifying such locations. Areas with the following characteristics have been identified and mapped: (1) within 10 kilometres of National Highways, (2) within 30 kilometres of broad gauge railway lines, (3) between 50 and 100 kilometres of cities with a population size of over one million, and within 30 to 60 kilometres of cities with a population size of over 300,000 but less than a million. Among the areas identified by these attributes, those with high agricultural potential have been excluded to figure out potential tracts in which SEZs could be located. The variables and the criteria could be changed as per a wider consensus derived from consultations with various stakeholders. It is argued that one of the options for states where the conflict between agricultural land and the felt need for industrialisation is high, is to choose industrial sectors such as information technology, bio-technology, the service sector and the like, that do not require much land as compared to manufacturing industries. A survey of the existing industrial estates in order to identify low performing or non-performing estates is also recommended. The results of the analysis also raise the question of whether a differential incentive package would be necessary to promote SEZs in areas that are at different levels of suitability.